A survey on perceptions of legal and non-legal factors affecting sustainable solid waste management in Malaysia - Intan Nadia Ghulam Khan; Wan Siti Adibah Wan Dahalan; Zulkifli Mohd Nopiah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Solid waste needs to be sustainably managed in order to mitigate its adverse impacts on the environment and human well-being. Sustainable solid waste management contributes to three important aspects of sustainable development, that is, environment, economic and social. It is clear that Malaysia aims to establish a sustainable solid waste management which is evident with the passing of the Solid Waste and Public Cleansing Management Act 2007 (Act 672). Act 672 introduces federalization and privatization of solid waste management in Peninsular Malaysia and Federal Territories of Putrajaya and Labuan. Nevertheless, various issues related with solid waste management in Malaysia give an indication that sustainable solid waste management is yet to be fully achievable in Malaysia. This study was conducted to examine level of perceptions of relevant authorities/ agencies of legal and non-legal factors affecting sustainable solid waste management in Malaysia. Collection of data for this study was conducted through face to face interview by using questionnaire and the circulation of the questionnaire form. The study finds that as the average of agreement percentage for six positive statements on legal factors affecting solid waste management in Malaysia is high, all the legal factors are important to facilitate the practice of sustainable solid waste management in Malaysia. Besides, the non-legal factors are also important considerations in facilitating sustainable solid waste management in Malaysia though by comparison, the percentage of agreement for legal factors is higher than non-legal factors.